Analyzes of the effects and security function social capital in sustainable rural border areas the villages of the central city of Saravan - Javad Bazrafshan; Mehrshad Toulabi Nejad (تحقیقات کاربردی علوم جغرافیایی, 2016)
The objective study was to investigate the effects of social capital on sustainability security in the villages the border areas. Statistical population including the villages of the central city of Saravan are heads of households (N= 9946). 421 households (23 villages) using Cochran formula and simple random sampling were selected. for the analysis data, descriptive and inferential statistics two methods (single sample t test, Pearson correlation and path analysis) is used. Results the research findings on the impact of social capital in rural sustainable security shows that the greatest impact is related to social security. Memorizing of patterns such a way that increases language, preservation of culture and religion, reducing drug use among youth, reduce the amount of conflict is between the people and so on. the lowest impact related to later economy. findings also show that dimension politico-military security partnership, trust and of cohesion between peoples and cooperation between police forces and and border guard to increase the political participation of the people, ethnic and sectarian narrow the gap, reducing illegal traffic in neighboring countries, increased cooperation with military forces in the fight against bandits and smugglers and maintain security and order is sent.